2007
DOI: 10.1063/1.2714782
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of subwavelength imaging with bilayered magnetic metamaterials: Theory and experiment

Abstract: We present a theoretical and experimental study of a bilayered metamaterial structure for subwavelength imaging of magnetic field. The simplest version of such a structure consists of one or two linear arrays of capacitively loaded split pipe resonators. Its subwavelength physics is governed by strongly anisotropic magnetic coupling between individual resonators and by propagation of magnetoinductive waves with wavelength much shorter than the wavelength of the electromagnetic radiation in free space. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 27 publications
4
47
0
Order By: Relevance
“…Occasionally, especially when the elements are very close, this coupling effect is not negligible and will have a substantial effect on the properties of the metamaterials. Recent studies have shown that the resonance coupling effect between split-ring resonators (SRR) can introduce magnetoinductive waves [10][11][12][13][14][15][16] In our previous theory work [27], another kind of coupling mechanism between resonance elements, …”
mentioning
confidence: 99%
“…Occasionally, especially when the elements are very close, this coupling effect is not negligible and will have a substantial effect on the properties of the metamaterials. Recent studies have shown that the resonance coupling effect between split-ring resonators (SRR) can introduce magnetoinductive waves [10][11][12][13][14][15][16] In our previous theory work [27], another kind of coupling mechanism between resonance elements, …”
mentioning
confidence: 99%
“…Applications have been identified in magnetic field concentration [18], delay-lines [19], phase shifters [20], filters and splitters [21] and near-field lenses [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This causes the coupling constant between resonators to become complex and leads to even more complicated dispersion [62]. Up to now, a series of microwave devices based on MI waves have been proposed, such as magneto-inductive waveguides [63], broadband phase shifters [64], parametric amplifiers [65], and pixel-to-pixel sub-wavelength imagers [66,67].…”
Section: Coherent Collective Waves In One-dimensional Meta-chainsmentioning
confidence: 99%